The seroprevalence of Japanese encephalitis virus in goats raised in Korea - Yang, Dong-Kun (The Korean Society of Veterinary Science, 2007)
Japanese encephalitis virus (JEV) causes a mosquito-borne viral zoonosis that is becoming increasingly important to public health in east and south Asia. Although JEV is primarily associated with reproductive failure in swine, JEV infection can cause fever and headache in humans and is associated with aseptic meningitis and encephalitis. The exact mode of transmission, including host range and possible source of viral amplification within livestock, is still not completely clear. This study consisted of a serological survey of JEV infection in goats. A total of 804 goat serum samples were collected from 144 farms in Korea between May 2005 and May 2006. The incidence of positive cases was 12.1% (97 out of 804 goats). The seroprevalence of JEV infection in the 144 farms screened was 31.3% (45/144), indicating that JEV infection is frequent in goat farms in Korea. In addition, three districts of Korea (mainly in the southern region) had a higher seroprevalence of JEV compared to other areas. The results suggest that goats could be monitored epidemiologically as a sentinel animal for JEV transmission in Korea.